Eluned Morgan and school education in Patagonia in the 19th century - Araújo, Sonia Maria da Silva (2023)
Based on the life experience of Eluned Morgan (1870-1938), writer, from a Welsh family, migrated to Argentina, Patagonia, Chubut Valley, the article deals with education in Latin America. The aime is to understand how education in Patagonia becomes an educational project by Eluned Morgan and reflect on the implications of this project in a region that was born under the impact of the National State with the“Conquest of the Desert”. Is based on cultural history and the history of intellectuals, as inspiration. The results demonstrate that Eluned Morgan assumes an important place in the region by using the pen of a writer to disseminate her educational ideas. Intellectually formed from a border view of the world, permeated by Welsh culture, Patagonian indigenous culture and Spanish-American culture, the writer defended education as a necessary instrument for the economic, social and cultural development of the Argentine South.